2018
DOI: 10.1073/pnas.1808402115
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale structure, mechanics, and transport properties of source rocks’ organic pore networks

Abstract: SignificanceIn source rocks, natural hydrocarbons are generated from organic matter dispersed in a fine-grained mineral matrix. The potential recovery of hydrocarbons is therefore influenced by the geometry of the organic hosted porous networks. Here, the three-dimensional structures of such networks are revealed using electron tomography with a subnanometer resolution. The reconstructions are first characterized in terms of morphology and topology and then used to build a multiscale simulation tool to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Nanopores with the radii < 5 nm do not increase gas flow rate, and do not increase the overall permeability of the source rock. Additionally, experimental and numerical results show the creation of the highly permeable channels close to larger nanopores (Berthonneau et al, 2018). Thus, the small nanopores must be connected to the larger nanopores as the continuous gas feeders, creating a multiscale network of pores and microcracks that together sustain long-term production from a horizontal gas well.…”
Section: Resultsmentioning
confidence: 99%
“…Nanopores with the radii < 5 nm do not increase gas flow rate, and do not increase the overall permeability of the source rock. Additionally, experimental and numerical results show the creation of the highly permeable channels close to larger nanopores (Berthonneau et al, 2018). Thus, the small nanopores must be connected to the larger nanopores as the continuous gas feeders, creating a multiscale network of pores and microcracks that together sustain long-term production from a horizontal gas well.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation techniques, such as horizontal drilling and hydraulic fracturing, could create fracture and to engender hydrocarbons migration to the wellhole [6,7]. Yet, the impressive progress of horizontal drilling and hydraulic fracturing technologies in the field of petroleum development have improved access to oil and gas from source rock formations [2,3,[8][9][10]. As a result, the proportion of hydrocarbons derived from unconventional reservoirs have been on the rise, and the knowledge about these reservoirs is gradually abundant [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…From a traditional perspective, the multitype tests could provide insight into the interplay among pore structures, lithology, physical property electric character, and hydrocarbon-bearing conditions [29][30][31][32]. In contrast to other unconventional reservoirs such as tight sandstone and tight carbonate reservoirs, the hydrocarbons which generated within organic agglomerates (kerogen) play a significant role [8,23,33]. Therefore, from a geochemical perspective, the pore structure data may show quantitative correlation with organic matter parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Contacts between the organic matter and the inorganic matter in these shales are the surfaces of mechanical weakness that are stimulated after hydrofracturing and expose nanopores to high permeability pathways. Berthonneau et al [29] showed that the largest pores are the potential crack areas at those weakness surfaces. These cracks create multiscale connectivity even at the pore scale.…”
Section: Introductionmentioning
confidence: 99%